2004
DOI: 10.1007/s11864-004-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for prevention of colorectal cancer: Pharmaceutical and nutritional interventions

Abstract: Interventions designed to delay or prevent the development of invasive colorectal adenocarcinoma might result in a profound impact on the incidence of and mortality from colorectal cancer. Current developmental efforts focus in two major directions: identification and testing of combination-targeted signal transduction pathway modulators and development of nutriceuticals. Both approaches recognize the heterogeneity of the carcinogenesis process. Combinations of agents (eg, aspirin or sulindac with DFMO, calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In CRC, one of the leading causes of cancer-related mortality in western countries, nutritional intervention offers great potential to delay or prevent the development of malignant processes; such an interventional strategy might result in a positive impact on the incidence of disease and mortality [28]. In this context, soybean BBI and related proteins have recently emerged as highly promising chemotherapeutic compounds within the GIT [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, one of the leading causes of cancer-related mortality in western countries, nutritional intervention offers great potential to delay or prevent the development of malignant processes; such an interventional strategy might result in a positive impact on the incidence of disease and mortality [28]. In this context, soybean BBI and related proteins have recently emerged as highly promising chemotherapeutic compounds within the GIT [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic investigation has shown that dietary, environmental and hereditary factors may play roles in the occurrence and development of colorectal cancer. 12,13 Molecular studies have also into specific details of the molecular mechanism warrant further investigation. In summary, CAC1 is highly expressed in colorectal cancer, and the expression status and localization of CAC1 protein show cyclic alteration with the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products and their compounds may act as a modulator of antitumorigenicity either as separate entities or by serving in synergism [ 22 ]. The combination of two or more components in drug design has also been proven to have clinically synergistic benefits against cancer treatment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%